VD_FINDINFO Jug / 2011 / 140 vom 18. Juli 2011 - VD Tribunal cantonal (2011)
RÉVISIONDÉCISION, MOTIF DE RÉVISION, MOYEN DE DROIT EXTRAORDINAIRE, OPPOSITIONPROCÉDURE | 386 al. 3 CPP (CH), 410 al. 1 let. a CPP (CH), 412 al. 2 CPP (CH)